Exploring Thermoelectric Property Improvement for Binary Copper Chalcogenides - Chen, Xinqi; Yang, Jianping; Katkus, Tomas; Wu, Tian; Tao, Junhui; Li, Jie; Wang, Chuanhui; Wang, Xin; Dai, Wei (Frontiers in Materials, 2020)
Copper chalcogenides have been the subject of extensive research as promising candidates in thermoelectric conversion applications due to their advantageous properties, environmental compatibility, and abundance. The low intrinsic thermal conductivity and high electric conductivity of these materials are born out of the “phonon-liquid electron-crystal” structure between the copper and chalcogens. In this review, strategies for thermoelectric property improvement of copper chalcogenides are discussed. The challenges and the future development of binary copper chalcogenides for further thermoelectric conversion applications are outlined.